2000
DOI: 10.1080/02724936.2000.11748155
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and spectrum of congenital heart disease in Oman

Abstract: We analysed the incidence and spectrum of congenital heart disease (CHD) in the Sultanate of Oman from 1994 to 1996. CHD was detected in 992 of 139,707 live births (incidence 7.1/1000 live births). The common CHDs were ventricular septal defect (24.9%), atrial septal defect (14.4%) and patent ductus arteriosus (10.3%). The frequency of atrioventricular septal defects (5.9%) was higher than reported from other countries. Age at diagnosis was under 1 month in 38% and 1-12 months in 40%. Cyanotic CHD was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 11 publications
3
27
0
1
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] [ Table 2] shows the prevalence of CHDs in India. [7][8][9][25][26][27][28][29][30] Studies in Chandigarh showed the maximum prevalence of 50.89 per 1000 live births [9] whereas studies in Shimla showed the minimum of 2.25 per 1000 live births.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] [ Table 2] shows the prevalence of CHDs in India. [7][8][9][25][26][27][28][29][30] Studies in Chandigarh showed the maximum prevalence of 50.89 per 1000 live births [9] whereas studies in Shimla showed the minimum of 2.25 per 1000 live births.…”
Section: Methodsmentioning
confidence: 99%
“…1 Other reported a relatively lower prevalence form different countires. [7][8][9][10][11][12] From India it has been reported a prevalence of CHD among their school going children of only 2.25 per 1000 child. 7 But in one community based study the investigators reported higher prevalence rate of CHD among Delhi children of 4.2 per 1000 of children.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Although going by figure quoted in western countries it has been generally accepted that approximately 10 per 1000 babies are born with CHD incase of full term births. 1 Other reported a relatively lower prevalence form different countires.…”
Section: Discussionmentioning
confidence: 99%
“…This valvar defect occurs sporadically in most cases however. There is a controversy whether consanguinity has an influence on the incidence of congenital heart disease; while some studies emphasized the increased risk in the rate of congenital cardiac malformations (Badaruddoza et al, 1994;Bassili et al, 2000;Gatrad et al, 1984), others failed to show such association (Robida et al, 1997;Subramanyan et al, 2000). Recent large case series demonstrated that parental consanguinity increases the risk of valvar aortic stenosis as well as atrial septal defect and tetralogy of Fallot, wich supports the involvement of autosomal recessive genes in its bearing (Nabulsi et al, 2003;Chehab et al, 2007).…”
Section: Introductionmentioning
confidence: 99%